2003
DOI: 10.1021/np0205598
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Dihydroisocoumarins Produced by Geotrichum sp., an Endophytic Fungus of Crassocephalum crepidioides

Abstract: Three novel dihydroisocoumarin derivatives (1-3) with antimalarial, antituberculous, and antifungal activities have been isolated by bioassay-guided fractionation from an endophytic fungus, Geotrichum sp., collected from Crassocephalum crepidioides. Structures were established as 7-butyl-6,8-dihydroxy-3(R)-pent-11-enylisochroman-1-one (1), 7-but-15-enyl-6,8-dihydroxy-3(R)-pent-11-enylisochroman-1-one (2), and 7-butyl-6,8-dihydroxy-3(R)-pentylisochroman-1-one (3) using spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 15 publications
2
62
0
3
Order By: Relevance
“…Mangrove-derived fungi and fungal-like organisms have been recognized as a repository of novel secondary metabolites, some of which have beneficial biological activities and recently numerous novel bioactive substances have been isolated from these microorganisms (Wagenaar & Clardy 2001, Brady et al 2001, Shrestha et al 2001, Kongsaeree et al 2003, Sridhar 2004, Kathiresan & Qasim 2005, Kim 2013, Saravanakumar & Kathiresan 2014. There are however, only limited studies on antioxidant potential of thraustochytrids.…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove-derived fungi and fungal-like organisms have been recognized as a repository of novel secondary metabolites, some of which have beneficial biological activities and recently numerous novel bioactive substances have been isolated from these microorganisms (Wagenaar & Clardy 2001, Brady et al 2001, Shrestha et al 2001, Kongsaeree et al 2003, Sridhar 2004, Kathiresan & Qasim 2005, Kim 2013, Saravanakumar & Kathiresan 2014. There are however, only limited studies on antioxidant potential of thraustochytrids.…”
Section: Introductionmentioning
confidence: 99%
“…The edible plant, Crassocephalum crepidioides S. MOORE (Japanese name; Benibanaborogiku), is wildly distributed in the Okinawa Islands and used in folk medicine for the treatment of acute hepatitis, fever and edema. Compounds with antimalarial activity and strong antimutagenicity had been isolated previously from C. crepidioides [1,2]. Other preparations from C. crepidioides have been described to have antioxidant and hepatoprotective properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…ITS sequences have been found to be a better marker for fungi than even the genes for ribosomal large and small subunits, since this region has good species resolution capabilities (Schoch et al 2012). Table III Although a few terrestrial plant endophytes have been shown to have antiplasmodial activity (Kongsaeree et al 2003;Cao et al 2011), our results show that endophytes colonizing seaweeds are equally a potential source to provide new leads against malaria. Further, our data suggest that antiplasmodial potential is more widespread across diverse fungal genera.…”
Section: Discussionmentioning
confidence: 73%